THE EFFECTIVENESS OF DIRECT PEER FEEDBACK TO INCREASE STUDENTS’ WRITING PERFORMANCE SUJITO (CORRESPONDING AUTHOR) - Emilia Yunita; sujito sujito (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2017)
This study intended to investigate if there was any significant difference between students’ writing performance who were treated using direct peer feedback and students writing performance who were treated using conventional method. The samples were X TKJ1 and X TKJ2 at SMK Mahardika Karangploso in the 2015/2016 academic year. In this study, the researcher used quasi-experimental research design to gain the data. The researcher implemented direct peer feedback in experimental group and conventional method in control group. Writing test as an instrument was used to collect the data. The research was conducted by the researcher for six meetings. Independent sample t-test was used to examine the data, the result showed that the mean score of experimental group was bigger than control group (82.17 > 71.38). Moreover, the sig.2-tailed value was less than 0.05 (0.000 < 0.05). It meant that there was significant differences between students’ writing performance who were treated using direct peer feedback and students’ writing performance who were treated using conventional method.